Podcasts e dupla excepcionalidade: uma análise documental sobre a disseminação de informações no Brasil - Barraca, Lígia Martins (Universidade Federal de São Carlos, 2025)
Recently, there has been growing a production and circulation of content in podcast format, along with an increasing use of this tool as a way of discovering new topics and conducting research for various purposes. One of the themes that has been gaining notoriety in this context is Twice Exceptionality. With that established, the main objective of this work was to analyze Brazilian podcasts that specifically address the topic of Twice Exceptionality, and, as a secondary objective, to investigate what content is covered in these podcasts and what purposes these materials serve when addressing the topic in question. This research has a documentary nature and was based on the collection and analysis of podcast episodes published between 2014 to 2024. The selection criteria included the presence of the terms “Dupla Excepcionalidade” (Twice Exceptionality) or “Dupla Condição” (Dual Condition) in the titles, the use of Brazilian Portuguese, and publication on the most widely used platforms in the country. The episodes were listened to and described, taking into account aspects such as the profile of the participants, the language used, and the target audience. The data indicate 17 productions found through the established criteria, and most episodes were produced by professionals in Psychology and Psychopedagogy, aimed at professionals in Education and Health as well as individuals with Twice Exceptionality Education. It was also found that there is a scarcity of specific content on the topic with the theme being explored in a superficial manner. The data collected highlighted the relevance of podcasts as an accessible and potentially effective tool for disseminating knowledge. Despite the limitations, it is inferred that there is a growing interest in the topic and, as a result, a possible trend toward the expansion of more in-depth content production on twice exceptionality.
Podcasts and twice excepcionality: docmental analysis about information propagation in Brasil
Keywords: Dupla excepcionalidade; Podcasts; Altas habilidade ou superdotação; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM